ENHANCING ORGANIZATIONAL STRUCTURE IN ELECTRONICS SERVICE COMPANIES: A CASE STUDY OF COMPANY X RECOMMENDATION USING HIERARCHICAL CLUSTER ANALYSIS - Darmawan, Calvienus Darrend; Tesavrita, Ceicalia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Company X is an electronics repair company with over 20 years of experience, based in Jakarta and Bekasi. In addition to repairs, Company X also engages in maintenance processes and the buying and selling of goods to both direct consumers and business clients. During the execution of work activities, several issues have arisen due to the lack of a proper internal management system. These issues are evident in the management aspects of POAC (Planning, Organizing, Actuating, and Controlling). Examples of these problems include the dual roles of an Owner, the absence of a standardized organizational structure, and the lack of clear job descriptions for all employees. To address these issues, a solution will be implemented using the Hierarchical Cluster Analysis method to produce a proposed organizational structure. The creation of this organizational structure will involve direct observation and interviews with Company X employees to gather data. Using the Hierarchical Cluster Analysis method, the selected dendrogram was the average linkage dendrogram. This dendrogram will serve as one of the bases for creating the proposed organizational structure, which will consist of five work departments. In addition to the proposed organizational structure, clear job descriptions will be defined in a job description table that outlines the duties, authorities, and responsibilities of each employee. Standard operating procedures will also be developed to standardize the newly proposed work activities. The overall output is expected to address the issues facing Company X and improve company performance.